Modernisasi dalam Sunah - Abdul Majid Khon (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
The modernization of Sunnah is an effort to renew the interpretation of Sunnah by purifying it from all kinds of superstitions, innovations (bid’ah), and myths. The modernization of Sunnah is divided into several areas of study, namely Sunnah related to social life, Sunnah āḥād which has a status of zhannī al-dilālah (probable indication), and Sunnah with an unclear status. Additionally, the modernization of Sunnah must be undertaken by experts in the sciences of Sunnah and Hadith, both in terms of narration (riwāyah) and comprehension (dirāyah).